Study of Prevalence of Placenta Previa and Circumstances among Pregnant Women in Fallujah Hospital (Indian Journal of Forensic Medicine & Toxicology, 2020)
Placenta previa refers to placenta which is totally or partly implanted in lower segment of the uterus.Mortality and morbidity of mother increase with placenta previa due to the increase in the incidence ofbleeding during pregnancy. This study aims to define placenta previa prevalence among pregnant womenat AL-Fallujah teaching hospital and to determine the risk factors and their association with placenta previaincidence in al-Fallujah city population.This retrospective cohort study investigated medical registry of 6339 gravid women in al-Fallujah teachingHospital in Iraq. We find 13 cases of placenta previa (0.21%) amongst the 6339 cases registered. The riskfactors that strongly appeared to affect the complication of pregnancy with placenta previa were; advancedmaternal age of ? 35, parity, previous curettage and previous cesarean section (P
Keywords: Prevalence, Placenta previa, Risk factors, maternal age, Parity, Previous curettage, previous cesarean section